Depression, anxiety, and stress among graduate adults preparing for competitive exams at libraries in a city of Central India: a cross-sectional study - Ramteke, Robin; Patle, Rupali; Divekar, Sachin; Narlawar, Uday (International Journal Of Community Medicine And Public Health, 2025)
Background: Graduate adults preparing for competitive examinations often face significant psychological stress due to prolonged self-study, performance pressures, and uncertainty about outcomes. These factors contribute to rising levels of depression, anxiety, and stress, which can adversely affect academic focus and quality of life. Methods: A descriptive cross-sectional study was conducted over four months (October 2024 to January 2025) in Nagpur among graduate adults preparing for competitive exams at public libraries. Using convenience sampling, five libraries were chosen from 196, recruiting 310 participants. Data were collected using the Depression, Anxiety, and Stress Scale (DASS-42), a validated self-administered questionnaire comprising 42 items. Descriptive statistics were used to calculate prevalence, and the significance level was set at p = 0.05. Results: Among the 310 participants, the prevalence of depression was 36.46%, anxiety 39.04%, and stress 33.23%. Female participants reported higher mean scores in all three domains compared to males. Medical graduates including MBBS, BAMS, BDS, nursing, and paramedical graduates experienced higher levels of psychological distress across depression, anxiety, and stress, whereas non-medical graduates from arts, commerce, and other science streams reported comparatively lower distress, with engineering students showing the least overall. Conclusions: The findings indicate a considerable prevalence of depression, anxiety, and stress among graduate students preparing for competitive exams. These results underscore the urgent need for regular mental health screening, early psychological intervention, and the establishment of counseling services in public study environments such as libraries.